MODEL OF STRENGTHENING HUMAN CAPITAL IN CREATIVE ECONOMIC DEVELOPMENT THROUGH THE ROLE OF HIGHER EDUCATION - Bakhri, Syaeful; Layaman, Layaman (IAIN Syekh Nurjati Cirebon, 2023)
AbstractThe creative economy has become a strategic issue in the era of Industrial Revolution 4.0 to compete in the face of international competition. Universities are expected to be able to develop society in the economic, social, cultural, and technological fields. This research aims to build diverse scientific references on current developments. Apart from that, this research focuses on strengthening human resources in developing the creative economy through the role of universities. This research uses a strategy mix method, combining quantitative and qualitative techniques. The regression analysis results show that the curriculum content has a significance value of 0.002, and the calculated t-value is 3.184, meaning that the curriculum content significantly affects resources. The significance value of resources is 0.000, and the t value is 4.458, meaning that resources significantly affect the creative economy. The coefficient of determination value is 0.173, meaning that the regression line equation explains 17% of variations in curriculum and resources that can influence the development of the creative economy in Cirebon Regency.Keywords: Human Capital; Creative Economy; Higher Education.